2020
DOI: 10.1186/s13578-019-0372-1
|View full text |Cite
|
Sign up to set email alerts
|

The antagonism of 6-shogaol in high-glucose-activated NLRP3 inflammasome and consequent calcification of human artery smooth muscle cells

Abstract: Background: Vascular calcification is the major reason for high mortality of cardiovascular complications for diabetes. Interleukin (IL)-1β has been implicated in this pathogenesis, but its precise role and clinical evidence have not been clearly identified. Hence, this study was aimed to investigate whether high concentration of glucose (HG), which mimics the hyperglycemia environment, could initiate vascular calcification through NLRP3/IL-1β inflammasome and the underlying mechanism. Recently, 6-shogaol, a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…142 In vitro experiments have revealed that high concentrations of glucose initiate the calcification in human vascular smooth muscle cells via upregulating the NLRP3 inflammasome-IL-1β axis. 143 6-shogaol reduces the calcification through attenuating the ROS production and downregulating the NLRP3 inflammasome. 143 The ginger-derived exosome-like nanoparticles (ELNs) also inhibit the NLRP3 inflammasome assembling, IL-1β, and IL-18 production as well as pyroptosis in the mouse macrophages.…”
Section: Anti-inflammatory Immunomodulatory and Anti-oxidative Potentials Of Gingermentioning
confidence: 99%
See 1 more Smart Citation
“…142 In vitro experiments have revealed that high concentrations of glucose initiate the calcification in human vascular smooth muscle cells via upregulating the NLRP3 inflammasome-IL-1β axis. 143 6-shogaol reduces the calcification through attenuating the ROS production and downregulating the NLRP3 inflammasome. 143 The ginger-derived exosome-like nanoparticles (ELNs) also inhibit the NLRP3 inflammasome assembling, IL-1β, and IL-18 production as well as pyroptosis in the mouse macrophages.…”
Section: Anti-inflammatory Immunomodulatory and Anti-oxidative Potentials Of Gingermentioning
confidence: 99%
“… 143 6-shogaol reduces the calcification through attenuating the ROS production and downregulating the NLRP3 inflammasome. 143 The ginger-derived exosome-like nanoparticles (ELNs) also inhibit the NLRP3 inflammasome assembling, IL-1β, and IL-18 production as well as pyroptosis in the mouse macrophages. 144 The ELN-related suppressive activity was largely attributed to its lipid fraction.…”
Section: Anti-inflammatory Immunomodulatory and Anti-oxidative Potentials Of Gingermentioning
confidence: 99%
“…43,44 Evidence shows that 6-shogaol can inhibit breast cancer cell invasion and exhibit an antagonistic effect in high-glucoseinduced NKRP3 inflammasomes in artery smooth muscle cells. 45,46 Although both hits were not novel chemicals, and their immunomodulatory role as well as their capacities to induce the expression of IFN-g have been extensively studied, it was still fortunate for us to detect them, which might help to validate the effectiveness of our screening model. In order to find novel potent chemicals, we need to expand the screening scale, but as least our primary screening data had encouraged us to continue the screening work.…”
Section: Discussionmentioning
confidence: 99%
“…6-shogaol has been reported to have higher radical scavenging effect and anti-inflammatory effect than gingerol [22]. In addition, 6-shogaol acutely relaxes airway smooth muscle and attenuates human artery smooth muscle cells calcification [23,24]. It has been reported that treatment of ginger extracts resulted in improvement of cellular differentiation of myoblast by cell cycle regulation [25].…”
Section: Discussionmentioning
confidence: 99%